Evaluasi Sistem Informasi Manajemen Keuangan Menggunakan Model Keberhasilan Sistem Informasi Delone dan Mclean: Tinjauan Literatur Sistematis - Ayu Wedia Ningsih; Hamdani Hamdani (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2026)
Financial Management Information Systems (FMIS) play a strategic role in enhancing organizational efficiency, transparency, accountability, and decision-making quality in financial management processes. This study aims to identify and analyze the factors influencing FMIS success based on the DeLone and McLean Information Systems Success Model. A Systematic Literature Review (SLR) approach following the PRISMA guidelines was employed using Scopus-indexed publications published between 2020 and 2026. An initial search yielded 334 articles, of which 10 studies met the inclusion criteria and were selected for in-depth analysis. Bibliometric analysis using VOSviewer was conducted to identify dominant research themes and relationships among key variables. The findings reveal that information quality, system quality, service quality, and user satisfaction are the most frequently examined determinants of FMIS success. Information quality emerged as the most influential factor, followed by system quality and service quality. Furthermore, successful FMIS implementation contributes to improved transparency, accountability, operational efficiency, organizational performance, and decision-making effectiveness. These findings confirm the continued relevance of the DeLone and McLean Model as a comprehensive framework for evaluating FMIS success across various organizational contexts.